Energy-efficient power control for two-tier femtocell networks with block-fading channels - Zhixin Liu; Jieshuai Wu; Yang Liu; Hongjiu Yang; Jianfeng Guan; Yu Wang (International Journal of Distributed Sensor Networks)
Femtocell network is an effective technique to improve spectrum utilization and indoor coverage. How to allocate users power while keeping acceptable performance under dynamic environment is still a challenge in practice. In this article, we study the problem of energy efficiency in a two-tier network. The objective of the article is to maximize energy efficiency for the two-tier femtocell network with the consideration of uncertain channels. The complex and dynamic communication environment will lead to the imperfect channel state information. In order to enhance the robustness of the two-tier network, we consider the imperfect channel state information of interference links in block-fading channels using probability constraints. We propose a novel scheme to derive optimal energy efficiency by transforming probability constraints into indicator function. A distributed iterative algorithm is proposed to obtain the optimal power solution. Numerical results illustrate the effectiveness of the proposed power control algorithm.